Alcohol and acute traumatic brain injury in the emergency department. (26th January 2021) - Rogan, Alice; Patel, Vimal; Birdling, Jane; Lockett, Jessica; Simmonds, Harnah; McQuade, David; Quigley, Paul; Larsen, Peter
Abstract: Objective: There is limited research from Australasian EDs describing the demographic make‐up, injury severity and impact of alcohol in patients requiring computed tomography (CT) for suspected traumatic brain injury (TBI). The present study aims to review the frequency and presenting patterns of patients who consume alcohol prior to presenting with suspected TBI. Methods: Retrospective observational study of patients referred for head CT to exclude TBI from a major referral centre and regional ED in New Zealand, between 1 September 2018 and 31 August 2019. Comparison groups were defined as 'alcohol involved' or 'no alcohol involved'. Results: 97/425 (22.8% [95% CI 18.3–27.4]) of included TBI presentations involved alcohol. 73/97 (75.3% [95% CI 58.6–93.5]) were male and 41/97 (42.3% [95% CI 29.3–55.2]) were aged 18–30 years. The alcohol group were more likely to report assault as the injury mechanism (19.6% [95% CI 10.8–28.4] vs 5.2% [95% CI 2.7–7.7], P < 0.05) and have Glasgow Coma Scale scores reflecting more moderate (13.5% [95% CI 5.9–21.1] vs 3.5% [95% CI 1.5–5.6]) and severe (5.6% [95% CI 0.7–10.5] vs 3.2% [95% CI 1.2–5.2] TBI. Presentation times post‐injury were delayed compared to the no alcohol group (3.4 h [interquartile range 1.9–14.8] vs 2.8 h [interquartile range 1.8–6.6], P < 0.05). Conclusion: One quarter of patients with suspected TBI had consumed alcohol prior to their injury. Predominantly, those affected were young males who reported higher rates of assault; however, alcohol use was recorded in all age groups and sex. Alcohol‐affected patients presented later, potentially delaying time to diagnosis. The present study supports the call for public health interventions that aim to reduce alcohol misuse. Abstract : The present study aimed to review the frequency and presenting patterns of patients who consume alcohol prior to presenting to ED with suspected TBI. One quarter of included patients with suspected TBI presenting to ED had consumed alcohol prior to their injury. Predominantly, those affected were young males who reported higher rates of assault; however, alcohol use was recorded in all age groups and sex. Alcohol‐affected patient presented later, potentially delaying time to diagnosis. The present study supports the call for public health interventions that aim to reduce alcohol misuse & improve ED screening.